2010
DOI: 10.1080/17470910903526155
|View full text |Cite
|
Sign up to set email alerts
|

Do you like me? Neural correlates of social evaluation and developmental trajectories

Abstract: Social acceptance is of key importance for healthy functioning. We used functional magnetic resonance imaging (fMRI) to examine age-related changes in the neural correlates of social acceptance and rejection processing. Participants from four age groups participated in the study: pre-pubertal children (8-10 years), early adolescents (12-14 years), older adolescents (16-17 years) and young adults (19-25 years). During the experiment, participants were presented with unfamiliar faces of peers and were asked to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
179
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(207 citation statements)
references
References 46 publications
28
179
0
Order By: Relevance
“…Our results for females have some support in the neuroimaging literature as well. For example, a linear increase with age has been found for activation in the striatum and vmPFC to rejection feedback when it was expected to occur (Gunther Moor et al, 2010). Finally, our findings are consistent with work documenting adolescents’ greater pupillary dilation in response to acceptance from a same-gender appraiser as opposed in response to an opposite-gender appraiser (Silk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results for females have some support in the neuroimaging literature as well. For example, a linear increase with age has been found for activation in the striatum and vmPFC to rejection feedback when it was expected to occur (Gunther Moor et al, 2010). Finally, our findings are consistent with work documenting adolescents’ greater pupillary dilation in response to acceptance from a same-gender appraiser as opposed in response to an opposite-gender appraiser (Silk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, following peer rejection, brain activity was found to increase from pre-pubescence to young adulthood in regions that support affect regulation (e.g., striatum, prefrontal cortex, and orbitofrontal cortex) (Gunther Moor et al, 2010). Other work has shown that neural activity in regions involved in social–cognitive processes (e.g., temporal parietal junction, TPJ) increased with age among females and decreased with age among males when accepted by peers with whom adolescents had not wanted to interact (Guyer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have examined neural responses to viewing or receiving Likes, and established that these Likes affect neural responses to information posted online. Receiving Likes on one’s picture or social media content, is associated with greater activation of reward circuitry, and these Likes influence attentional focus (Gunther Moor et al , 2010; Silk et al , 2011; Achterberg et al , 2016; Sherman et al , 2016). Even Likes on strangers’ photos influence neural and behavioral responses: we previously reported that when young people viewed Instagram photos with many Likes, compared with few, they showed greater responses in brain regions associated with reward and visual attention, and were themselves more likely to click Like (Sherman et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of prior studies have examined the effects of social rejection on the brain and other physiological systems (Eisenberger van Leijenhorst, et al, 2010;Guyer et al, 2009;Masten et al, 2009Masten et al, , 2010Somerville et al, 2006;Stroud et al, 2009), these studies have generally focused on adults or adolescents without psychopathology, and on brain regions such as the anterior cingulate cortex rather than subcortical regions such as the amygdala, which is clearly a focal point for the neural basis of anxiety disorders (Davidson, 2002;Freitas-Ferrari et al, 2010;Monk, 2008;Pine et al, 2009). Our data clearly demonstrate a pattern of aberrant activity in the amygdala-hippocampal complex in response to peer rejection in anxious adolescents.…”
Section: Discussionmentioning
confidence: 99%